2015
DOI: 10.1021/acsami.5b06413
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Evaporation Method for Large-Scale Production of Liquid Crystalline Lipid Nanoparticles with Various Internal Structures

Abstract: We present a simple and industrially accessible method of producing liquid crystalline lipid nanoparticles with various internal structures based on phytantriol, Pluronic F127, and vitamin E acetate. Bilayer vesicles were produced when an ethanolic solution dissolving the lipid components was mixed with deionized water. After the evaporation of ethanol from the aqueous mixture, vesicles were transformed into lipid-filled liquid crystalline nanoparticles with well-defined internal structures such as hexagonal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…The onset, peak, and offset temperatures for the phase transition can be found (Figure B) as well as the enthalpy (estimated here as 0.5 mJ mg −1 or 150 J mol −1 based on phytantriol) from integrating the heat capacity curve (Figure C). Literature microcalorimetry data for phytantriol mesophase systems were reported by Doo‐Hoon on cubosomes. However, transition data were not unequivocally assigned as cubic to hexagonal.…”
Section: Resultsmentioning
confidence: 94%
“…The onset, peak, and offset temperatures for the phase transition can be found (Figure B) as well as the enthalpy (estimated here as 0.5 mJ mg −1 or 150 J mol −1 based on phytantriol) from integrating the heat capacity curve (Figure C). Literature microcalorimetry data for phytantriol mesophase systems were reported by Doo‐Hoon on cubosomes. However, transition data were not unequivocally assigned as cubic to hexagonal.…”
Section: Resultsmentioning
confidence: 94%
“…The dispersed hexosomes were successfully prepared by Kim et al when adding VitEA to PT-Pluronic F-127 (stabilizer)-water systems. 79 The inuence of hexadecane in PT and GMO was investigated respectively by Phan et al 22 SAXS data indicated that in GMOwater systems at 25 C, Pn3m, H 2 , micellar cubic phase (Fd3m), and inversed micelles (L 2 ) appeared when the concentration of hexadecane was 0-4% (w/w), 4-25%, 25-40% and >40% respectively. However, with an increase in the concentration of hexadecane in PT-water systems, the phase transitioned from Pn3m to H 2 to L 2 without forming the micellar cubic phase.…”
Section: Prescription Factorsmentioning
confidence: 99%
“…38 However, because of bulk-scale mixing of ethanol and water, this method also results in high polydispersity of particle sizes. 36,37…”
mentioning
confidence: 99%